Excise Tax and Fire Safety Education Program Budgets - Walker, Rob (Tufts Archival Research Center, 2007)
Draft; Explanations of budget items and cost estimates for the Tobacco Institute Excise Tax and Economics Program and their Fire Safety Education Program. Compares 1995 levels to 1996 levels. Identifies goals of programs and summarizes background and recommendations. Breaks excise tax program into general economic data and support, the cross-border program, the social costs argument, and work with allied organizations.